Stratified Cox Model with Interactions in Analysis of Recurrent Events - Bieszk‑Stolorz, Beata (Acta Universitatis Lodziensis. Folia Oeconomica, 2018)
The purpose of this paper is the assessment of relative intensity of exit from registered unemployment by means of the analysis of recurrent survival episodes and the comparison of these results with the results obtained for an individual episode. The stratified Cox model with interactions was used. Statistical data collected by labour offices indicate that a large fraction of the unemployed persons is registered multiple times. However, many of them resign from the mediation of labour offices and are subsequently removed from the register. In the article, the intensities of de‑registration due to various causes for men and women were compared. The study data came from the database of personal details of people registered by the Poviat Labour Office in Szczecin in 2013. The observation covered the records of their registration until the end of 2014. Gender of the unemployed persons influenced the intensity of de‑registrations in the first episodes, partially in the second and third ones, due to various causes, such as finding a job or removal from the register, whereas it did not influence the intensity of de‑registrations in the fourth and subsequent episodes. As for the other causes in the subsequent episodes, the differences were also not statistically significant. The proposed analysis may be important for implementing a good policy in the labour market. The identification of persons that resign from the mediation of the labour office is as interesting as the identification of these persons who find a job.